Missouri's Quail Hunter Cooperator Survey - Thomas V. Dailey (National Quail Symposium Proceedings, 2017)
Since 1938, Missouri has surveyed northern bobwhite ( Colinus virginianus) hunters to learn of hunter demographics and hunting success. This information is useful for identifying long-term trends in hunting activity and for planning future hunting recreation and regulations. In this paper, I evaluate temporal variation in hunting success within and among hunting seasons. The survey was generated from daily hunting journals of 200 to 600 quail hunters. On a week-by-week basis, cooperators harvest most quail during the first week of the season. Hunting has consistently been concentrated in a handful of days including the first and last 2 days of the season, Saturdays, Sundays, and holiday weekends. The rate at which quail were found decreased with time during the hunting season. Comparing hunters from metropolitan and rural areas, hunting activity and success have changed with time. During 1938 to 1944, city hunters spent less time in the field and found and bagged quail at a lower rate than did rural hunters. During the 1980's, however, city hunters spent more time in the field and found and bagged quail at a rate almost equal to that of rural hunters. I discuss implications of various trends in hunting activity for management of hunting recreation.